Review and Derivation of Areal Reduction Factor in Malaysia with Response to Changing Climate - Kok K.; Yu W.; Sidek L.M.; Jung K. (Springer Verlag, 2023)
Climate change; Spatial variables measurement; Storms; Areal reduction factors; Design applications; Rainfall characteristics; Rainfall patterns; Spatial autocorrelations; Time-series data; Tracking method; Trend tests; Rain